Usability testing for library websites : a hands-on guide - Norlin, Elaina (American Library Association, 2002)
Unless you're the librarian who set them up, online library services can be hard to navigate. In fact, many users give up in frustration without ever finding what they're looking for. Nowadays, many of the search and retrieval services that previously were database-driven are now Web-based and part of the library's official Web site. So as libraries increasingly use the Web to deliver both in-house and remote services online, it is critical that their sites are engaging, easy to navigate, and created with the end user--the library customer--in mind. This soup to nuts guide will help beginners an.